2018
DOI: 10.1016/j.joca.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Association of childhood adiposity measures with adulthood knee cartilage defects and bone marrow lesions: a 25-year cohort study

Abstract: Childhood adiposity measures were associated with the increased risk of adulthood patellar cartilage defects and, to a lesser extent, BMLs, independent of adulthood adiposity measures. These results suggest that adiposity in childhood has long-term effects on patellar structural abnormalities in young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…One study also investigated the effects of childhood obesity on knee structural pathology in adult life. Meng et al evaluated 327 subjects from the Australian Schools Health and Fitness Survey (ASHFS) and found that childhood obesity was associated with an increased risk of adulthood patellar cartilage defects and patellar bone marrow edema lesions on MRI 8 .…”
Section: Obesity In Knee Oamentioning
confidence: 99%
“…One study also investigated the effects of childhood obesity on knee structural pathology in adult life. Meng et al evaluated 327 subjects from the Australian Schools Health and Fitness Survey (ASHFS) and found that childhood obesity was associated with an increased risk of adulthood patellar cartilage defects and patellar bone marrow edema lesions on MRI 8 .…”
Section: Obesity In Knee Oamentioning
confidence: 99%
“…Knees were imaged on a 1.5 T whole-body magnetic resonance unit with use of a commercial transmit-receive extremity coil. The Knee cartilage defects were measured as previously reported [22] in an ordinal scale using the T1-weighted spoiled gradient-recalled sagittal MR images and proton density-weighted fast spin-echo coronal MR images together. Grade 0 indicated a normal cartilage.…”
Section: Mri Measurementsmentioning
confidence: 99%
“…However, most of these studies have focussed on the association between obesity and OA in adults, and little is known about the risk of obesity and OA in childhood. Observational studies have shown that childhood obesity is associated with knee joint pain, stiffness, and dysfunction in adulthood [ 11 , 12 ]. However, those studies could be affected by confounders, such as health and nutritional status, which could result in a potential relationship of reverse causality.…”
Section: Introductionmentioning
confidence: 99%